Development of interactive media based on lectora inspire software using the addie model - Pratita, Dewi; FH, Yuliana; Deskoni, Deskoni (SEAN Institute, 2024)
This study aims to determine the level of validity and effectiveness of interactive learning media using the developed lectora inspire software. This research is a development research using the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The instruments used in this study were validation sheets, questionnaires, observation sheets and test sheets. The results showed that the average value of material expert validation was 95% and the average value of design expert validation was 85.45% which means that the interactive media developed is suitable for use in the field but with revisions from some expert advice. The results of observations made on student learning activity using interactive media amounted to 87.7% with a very good category. Based on the results of an open questionnaire distributed to students in a limited trial, it was found that students were enthusiastic and enthusiastic about learning using interactive media, this means that the developed media is very well used in Digital Learning lectures. The results of field trials stated that the medial developed was feasible for use with an average student response of 87.05% answering very interested in learning using interactive learning media developed so that it could be understood by students. Based on the results of the study, it can be concluded that interactive media using lectora inspire which was developed is categorized as valid and effective so that it is very good to be used in the Digital Learning lecture process.